Analiza prawnoporównawcza współdziałania w popełnieniu przestępstwa - Slavković, Vukan (Czasopismo Prawa Karnego i Nauk Penalnych, 2021)
The paper analyses the main provisions of complicity in the criminal law of Great Britain, the United States, France, and Germany. The norms on responsibility for crimes committed by a group of persons, regardless of whether they are regulated by the common law or the Romano-Germanic legal system, were largely influenced by the accessory theory of complicity. The criminal legislation of Great Britain and the United States considers incitement, conspiracy, and attempt not as stages of committing crimes but as independent criminal offenses entailing punishment. There are many similarities between the British and French laws on accomplice liability. Both systems have the same starting point, what French scholars would describe as l’emprunt de la responsabilité, which can literally be translated as ‘the borrowing of liability’. This is a way of explaining that the liability of the accomplice is dependent on the liability of the principal offender: without a principal offense, there can be no liability for complicity. Although the terminology is different, the law in both systems essentially covers the help or encouragement provided before or at the time of the principal offense. Once found liable, the accomplices are punished as if they were the principal offenders. Contrary to the criminal law of the United States and Germany, in French law, the act of complicity must have been accomplished and not merely attempted. In Germany, courts have long relied on subjective factors to draw distinctions between the forms of complicity: In order to be a perpetrator of any kind, it is necessary, according to long-standing jurisprudence, to have the mindset of a perpetrator (animus auctoris) or the will to commit the offense oneself. The characteristic of a mere accomplice, in contrast, is that a person has the will to support another (animus socii).